Effects of 5-Hydroxymethylcytosine Epigenetic Modification on the Stability and Molecular Recognition of VEGF i-Motif and G-Quadruplex Structures - Morgan, Rhianna K.; Molnar, Michael M.; Batra, Harshul; Summerford, Bethany; Wadkins, Randy M.; Brooks, Tracy A. (Journal of Nucleic Acids, 2018)
Promoters often contain asymmetric G- and C-rich strands, in which the cytosines are prone to epigenetic modification via methylation (5-mC) and 5-hydroxymethylation (5-hmC). These sequences can also form four-stranded G-quadruplex (G4) or i-motif (iM) secondary structures. Although the requisite sequences for epigenetic modulation and iM/G4 formation are similar and can overlap, they are unlikely to coexist. Despite 5-hmC being an oxidization product of 5-mC, the two modified bases cluster at distinct loci. This study focuses on the intersection of G4/iM formation and 5-hmC modification using the vascular endothelial growth factor (VEGF) gene promoter’s CpG sites and examines whether incorporation of 5-hmC into iM/G4 structures had any physicochemical effect on formation, stability, or recognition by nucleolin or the cationic porphyrin, TMPyP4. No marked changes were found in the formation or stability of iM and G4 structures; however, changes in recognition by nucleolin or TMPyP4 occurred with 5-hmC modification wherein protein and compound binding to 5-hmC modified G4s was notably reduced. G4/iM structures in the VEGF promoter are promising therapeutic targets for antiangiogenic therapy, and this work contributes to a comprehensive understanding of their governing principles related to potential transcriptional control and targeting.